Efektivitas Bina Keluarga Lansia (BKL) terhadap Kualitas Hidup Lansia - Desy Tariustanti; Zarah Puspitaningtyas; Al Munawir (Multidisciplinary Journal, 2021)
Elderly family development is a group of family activities including the elderly and the elderly themselves which aims to improve knowledge, attitudes and behavior or family skills in order to improve the quality of life. the lives of the elderly. Elderly Family Development is a forum for the elderly to live healthy, active, productive and independent lives through group activities. The CoE Aging Family Development Program integrates a number of cross-sectoral activities, especially by coordinating with relevant agencies representing the government. Improving the quality of life as the goal of implementing health control programs is influenced by several factors, including physical, psychological, social and environmental. This research is a descriptive study with a qualitative approach which was carried out in the Drupadi Elderly Family Development group in Mimbaan Village. Research informants are the main informants for the elderly and their families, who provide additional information, namely midwives, curative practitioners and health service providers. family development for the elderly. The main informant is the Head of the Population and Family Planning Agency. The results showed that the Elderly Family Development program had an effect on the quality of life of the elderly. This was obtained from the results of in-depth interviews with key informants, additional informants and key informants. According to the informant, the activities of the health service program are very diverse so that the elderly are very enthusiastic to participate with the total number of participants for each activity is 70%. The results of in-depth interviews show that BKL has succeeded in improving the quality of life of the elderly. This can be seen from the narratives of informants and the daily activities of the elderly who are increasingly productive.